Plaster cast versus functional bracing for Achilles tendon rupture: the UKSTAR RCT. - Costa, ML; Achten, J; Wagland, S; Marian, IR; Maredza, M; Schlüssel, MM; Liew, AS; Parsons, NR; Dutton, SJ; Kearney, RS; Lamb, SE; Ollivere, B; et al. (National Institute for Health Research, 2020)
BACKGROUND: Achilles tendon rupture affects > 11,000 people each year in the UK, leading to prolonged periods away from work, sports and social activities. Traditionally, the ruptured tendon is held still in a plaster cast for ≥ 8 weeks. Functional bracing is an alternative treatment that allows patients to mobilise earlier, but there is little evidence about how bracing affects patients' recovery.